A cobalt-containing two-dimensional conjugated phthalocyanine framework and its preparation method and application

Cobalt-containing two-dimensional conjugated phthalocyanine framework (CoSAs-CPF) prepared by solvothermal method as artificial SEI solves the problems of poor SEI stability and lithium dendrites in lithium metal batteries, and achieves higher Li+ adsorption capacity and cyclic stability.

CN118908963BActive Publication Date: 2025-04-15HUAZHONG UNIV OF SCI & TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410982037.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-04-15
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

Lithium metal batteries have a rapid capacity degradation and safety hazards due to poor stability of solid electrolyte interface (SEI) and uncontrolled growth of lithium dendrites, which limit their commercial applications.

Method used

A two-dimensional conjugated phthalocyanine frame (CoSAs-CPF) containing cobalt was prepared by solvothermal method and used as an artificial solid electrolyte interface (SEI) to enhance adsorption to Li+ and inhibit the growth of lithium dendrites.

Benefits of technology

By using CoSAs-CPF as SEI, the adsorption capacity to Li+ is significantly enhanced, the growth of lithium dendrites is inhibited, and the circulation stability and safety of lithium metal batteries is improved, which is better than most of the reported SEI films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908963B_ABST
    Figure CN118908963B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium ion batteries, and specifically relates to a cobalt-containing two-dimensional conjugated phthalocyanine framework and a preparation method and application thereof, comprising the following steps: using 1,2,4,5-tetracyanobenzene and a soluble cobalt salt as raw materials, and 1,8-diazacyclo (5,4,0) undec-7-ene as a catalyst, a solvothermal reaction is carried out in an organic solvent to obtain the cobalt-containing two-dimensional conjugated phthalocyanine framework. The present invention develops a two-dimensional conjugated phthalocyanine framework containing a single cobalt atom as a new type of artificial solid electrolyte interface. Due to the Lewis acid activity of the Co metal site and the strong electron absorption characteristics of the cyano group, a large amount of charge is transferred to the CPF framework, which greatly enhances the Li + adsorption and regulate Li + distribution toward dendrite-free Li metal batteries, outperforming most reported SEI films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a cobalt-containing two-dimensional conjugated phthalocyanine framework and a preparation method and application thereof. Background Art

[0002] The development of portable electronic devices and electric vehicle technologies has spawned a huge demand for high energy density energy storage systems. –1 ) and low redox potential (3.04 V vs SHE), lithium metal batteries have been recognized as one of the most attractive candidate materials for high energy density energy storage devices. However, due to the poor stability of the solid electrolyte interface (SEI) and the uncontrolled growth / crushing of lithium dendrites, the capacity of lithium metal batteries rapidly degrades, which also brings potential safety hazards, limiting the further commercial application of lithium metal batteries.

[0003] To address these issues, a variety of strategies have been adopted to enhance the SEI layer by using various electrolyte additives or novel lithium-philic current collectors. Although these strategies have improved the uniform deposition of lithium and the cyclability of lithium metal batteries to some extent, the in-situ generated heterogeneous organic-inorganic hybrid SEIs are still insufficient to suppress the growth of needle-like dendrites. In this context, artificial SEI membranes are considered to be an efficient way to solve the lithium anode interface problem for the following reasons: (1) the chemical composition of artificial SEI membranes is uniform, which is conducive to the uniform diffusion of lithium metal; (2) better morphological structures can be obtained through reasonable design, improving the electrochemical performance of the electrode interface; (3) the contact between the electrolyte and the electrode material can be effectively isolated, reducing the electrolyte reaction, thereby improving the Coulombic efficiency. However, it should be noted that it is challenging to prepare artificial SEI membranes that can simultaneously meet all the above requirements. In recent years, graphene films, Al2O3 and lithium alloys have been widely used as stable SEI membranes to isolate unexpected side reactions and protect lithium anodes, and have also made significant progress in improving the interface stability of lithium metal batteries. However, how to achieve better chemical compatibility, more substantial lithium ion transport efficiency and more uniform lithium ion deposition still limits the practical application of artificial SEI films. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a cobalt-containing two-dimensional conjugated phthalocyanine framework and its preparation method and application. The cobalt-containing two-dimensional conjugated phthalocyanine framework is prepared by a solvothermal method and used as an artificial solid electrolyte interface (SEI) to enhance the Li + The adsorption of lithium ions inhibits the growth of lithium dendrites.

[0005] The present invention is specifically achieved through the following technical solutions.

[0006] The first object of the present invention is to provide a method for preparing a two-dimensional conjugated phthalocyanine framework containing cobalt, wherein the two-dimensional conjugated phthalocyanine framework containing cobalt is used to prepare an artificial solid electrolyte interface of a high-voltage lithium metal battery, comprising the following steps:

[0007] The cobalt-containing two-dimensional conjugated phthalocyanine framework is prepared by using 1,2,4,5-tetracyanobenzene and soluble cobalt salt as raw materials and 1,8-diazacyclo(5,4,0)undec-7-ene as a catalyst in an organic solvent through a solvothermal reaction.

[0008] The present invention adopts a solvothermal method to synthesize a two-dimensional conjugated phthalocyanine framework containing a single cobalt atom. The method is simple and does not require thermal decomposition. The Co single atom is effectively stabilized in the ultra-thin two-dimensional structure, which can ensure a higher atomic utilization rate and provide a more effective charge transfer pathway. The mild synthesis route effectively reduces the agglomeration of CoSAs-CPF and ensures the utilization rate of the metal site.

[0009] The cobalt-containing two-dimensional conjugated phthalocyanine framework of the present invention is used as an artificial solid electrolyte interface (SEI). Due to the Lewis acid activity of the Co metal site and the strong electron absorption characteristics of the cyano group (-CN), a large amount of charge is transferred to the skeleton of the conjugated phthalocyanine framework material, which greatly enhances the Li + The adsorption of lithium ions inhibits the growth of lithium dendrites.

[0010] In a preferred embodiment of the present invention, 1,2,4,5-tetracyanobenzene and Co 2+ The molar ratio of 1,2,4,5-tetracyanobenzene and the catalyst 1,8-diazacyclo(5,4,0)undec-7-ene is 2:1.

[0011] In a preferred embodiment of the present invention, the reaction temperature is 100-240° C., and the reaction time is 2-6 days.

[0012] In a preferred embodiment of the present invention, the soluble cobalt salt is one of cobalt chloride, cobalt nitrate and cobalt sulfate.

[0013] In a preferred embodiment of the present invention, the organic solvent is a mixed solvent prepared by ethylene glycol and DMF in a volume ratio of 1-9:1.

[0014] In a preferred embodiment of the present invention, the dosage ratio of 1,2,4,5-tetracyanobenzene to the organic solvent is 0.1 g: 5-30 mL.

[0015] The second object of the present invention is to provide a cobalt-containing two-dimensional conjugated phthalocyanine framework prepared by the preparation method.

[0016] The third object of the present invention is to provide a method for preparing an artificial solid electrolyte interface of a high-voltage lithium metal battery, wherein the cobalt-containing two-dimensional conjugated phthalocyanine framework is dispersed in DMF and subjected to ultrasonic treatment to form a nanosheet mixed solution; after filtering the nanosheet mixed solution, the nanosheet is transferred to the lithium surface by a roller pressing process, and finally the artificial solid electrolyte interface of the high-voltage lithium metal battery is prepared.

[0017] The fourth object of the present invention is to provide an artificial solid electrolyte interface for a high-voltage lithium metal battery prepared by the above preparation method.

[0018] A fifth object of the present invention is to provide an application of the artificial solid electrolyte interface of the high-voltage lithium metal battery in a high-voltage lithium metal battery.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses 1,2,4,5-tetracyanobenzene and soluble cobalt salt as raw materials and 1,8-diazacyclo(5,4,0)undec-7-ene as a catalyst to synthesize a two-dimensional conjugated phthalocyanine framework (CoSAs-CPF) containing a single cobalt atom by a solvothermal method. It is used as a new type of artificial solid electrolyte interface (SEI). Due to the Lewis acid activity of the Co metal site and the strong electron absorption characteristics of the cyano group (-CN), a large amount of charge is transferred to the skeleton of the conjugated phthalocyanine framework material, which greatly enhances the Li + The adsorption of lithium ions can inhibit the growth of lithium dendrites, which is better than most reported SEI films.

[0021] (2) The present invention adopts a solvothermal method to synthesize a two-dimensional conjugated phthalocyanine framework containing a single cobalt atom. The method is simple and does not require thermal decomposition. The Co single atom is effectively stabilized in the ultra-thin two-dimensional structure, which can ensure higher atomic utilization and provide a more effective charge transfer pathway. The mild synthesis route effectively reduces the agglomeration of CoSAs-CPF and ensures the utilization of metal sites.

[0022] (3) The strategy of constructing CoSAs-CPF enhanced lithium anode in the present invention provides a promising direction for the further development of high energy density and high voltage lithium metal batteries with long cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 In the figure, a is a schematic diagram of lithium during the synthesis of MSAs-CPF (M = Fe, Cu, Zn, Ni, Co), b is the binding energy of lithium atoms on MSAs-CPF and MSAs-CN-CPF, and c is the migration energy barrier of lithium on CoSAs-CPF, NiSAs-CPF and CuSAs-CPF.

[0024] Figure 2In the figure, a is a schematic diagram of a lithium metal battery based on CoSAs-CPF, b is a schematic diagram of the manufacturing process of CoSAs-CPF@Li, and c is the mechanism of lithium deposition process of lithium metal battery CoSAs-CPF@Li.

[0025] Figure 3 In the figure, a is the high-resolution Co 2p spectrum of CoSAs-CPF, the black curve is the fitting data, the gray line is the experimental result, b is the standardized XANES, c is the Co K-edge radial structure function obtained by Fourier transform of the k3-weighted EXAFS results with Co foil, Co2O3, Co3O4 and CPFc as references, d is the AFM image of CoSAs-CPF, e is the TEM of CoSAs-CPF, f is the HR-TEM image of CoSAs-CPF with annotated single atoms, g is the HAADF STEM image, and h, i are the EDS mapping results of CoSAs-CPF.

[0026] Figure 4 In the figure, a is the constant current cycling curve of the CoSAs-CPF modified lithium-lithium symmetric battery; b is the rate capability of the lithium symmetric battery with CoSAs-CPF@Li, NiSAs-CPF@Li and bare lithium; c and d are the depth profile XPS data of the cycled bare lithium anode and CoSAs-CPF@Li, respectively; e.g. are the top view SEM images of the bare lithium anode, NiSAs-CPF@Li and CoSAs-CPF@Li after cycling, respectively.

[0027] Figure 5 where a is LFP||CoSAs-CPF@Li, LFP||NiSAs-CPF@Li and LFP||bare lithium (20 mg cm -2 ) at 1°C; b is the cycling performance of LFP||CoSAs-CPF@Li (30 mg cm -2 ) at 1°C; c is the cycling performance of NCM811||CoSAs-CPF@Li, NCM811||NiSAs-CPF@Li and NCM811||bare lithium (10 mg cm -2 ) at 1°C; d is the cycling performance of NCM811||CoSAs-CPF@Li (10 mg cm -2 ) rate performance; e is the cycling performance of NCM811 at 1°C || CoSAs-CPF@Li (20 mg cm -2 )f) Performance comparison of coin cell with NCM811 cathode.

[0028] Figure 6In the figure, a is the optical image of the NCM811 pouch battery, b and c are the charge and discharge curves and cycle performance of the NCM811||CoSAs-CPF@Li pouch battery, respectively; df are the in situ ultrasonic transmission images of NCM811||bare lithium (d), NCM811||NiSAs-CPF@Li (e), and NCM811||CoSAs-CPF@Li (f) before 60 cycles, respectively; gi are the top view and cross-sectional SEM images of bare lithium (g), NiSAs-CPF@Li (h), and CoSAs-CPF@Li (i) after 60 cycles, respectively.

[0029] Figure 7 Figure 2 is the difference in electron density between Li atoms and the CPF surfaces of different MSAs, where the cyan and yellow areas represent electron depletion and accumulation, respectively.

[0030] Figure 8 Li on the surface of CoSAs-CPF + Gibbs spectrum of the intermediate structure during the migration process.

[0031] Fig. 9 The surface Li of NiSAs-CPF + Gibbs spectrum of the intermediate structure during the migration process.

[0032] Fig.10 The surface Li of CuSAs-CPF + Gibbs spectrum of the intermediate structure during the migration process.

[0033] Fig.11 Li on the surface of CuSAs CPF + Top and side views of the structures in the middle of the migration process.

[0034] Fig.12 Li on the surface of NiSAs CPF + Top and side views of the structures in the middle of the migration process.

[0035] Fig.13 Li on the surface of CoSAs CPF + Top and side views of the intermediate structures during migration.

[0036] Fig.14 This is the infrared nuclear magnetic spectrum of CoSAs-CPF.

[0037] Fig.15 For CoSAs-CPF 13 C NMR spectrum.

[0038] Fig.16Wavelet transform of the χ(k) spectra of CoSAs-CPF, Co-Pc, Co-foil, Co2O3, and Co3O4.

[0039] Fig.17 This is the SEM image of CoSAs-CPF.

[0040] Fig.18 This is the SEM image of CoSAs-CPF.

[0041] Fig.19 is the thickness of CoSAs-CPF.

[0042] Fig. 20 Optical photograph of CoSAs-CPF@PP.

[0043] Fig.21 Optical photograph of the CoSAs-CPF artificial solid electrolyte interface.

[0044] Fig. 22 This is a cropped optical photograph of CoSAs-CPF@Li.

[0045] Fig.23 is the contact angle of Li chip and CoSAs-CPF@PP.

[0046] Fig.24 High-resolution C1s spectra of CoSAs-CPF and CoSAs-CPF@Li.

[0047] Fig.25 High-resolution N1s spectra of CoSAs-CPF and CoSAs-CPF@Li. DETAILED DESCRIPTION

[0048] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0049] The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0050] High-voltage lithium metal batteries are ideal for the next generation of high-energy rechargeable batteries, but their capacity is severely reduced due to poor interface stability and compatibility between electrodes and electrolytes, limiting their practical applications. The present invention uses 1,2,4,5-tetracyanobenzene and soluble cobalt salts as raw materials, 1,8-diazacyclo(5,4,0)undec-7-ene as a catalyst, and a solvothermal method to synthesize a two-dimensional conjugated phthalocyanine framework (CoSAs-CPF) containing a single cobalt atom. It is used as a new type of artificial solid electrolyte interface (SEI). Due to the Lewis acid activity of the Co metal site and the strong electron absorption characteristics of the cyano group (-CN), a large amount of charge is transferred to the skeleton of the conjugated phthalocyanine framework material, which greatly enhances the Li + The adsorption of lithium ions can inhibit the growth of lithium dendrites, which is better than most reported SEI films.

[0051] In order to study the adsorption effect of lithium on conjugated pseudophthalocyanine frameworks based on different metal centers (MSAs-CPF, M=Fe, Co, Ni, Cu, Zn) Figure 1 In (a), the evaluation indicators of adsorption energy and migration energy barrier were obtained by charge decomposition analysis (CDA) and density functional theory (DFT) calculations. The differential charge density map shows the electron density distribution between lithium and CPF-M, as well as the limited charge accumulation in the framework, clearly indicating that the adsorption process is accompanied by charge transfer of Li-M-N3 ( Figure 7 ). Subsequently, the adsorption energy of lithium on the MSAs-CPF surface was determined by DFT. Figure 1 As shown in (b), all metal sites show strong adsorption energy effects on lithium, indicating that these metals are lithiophilic. Among them, the adsorption energy of the CoSAs-CPF-based system is relatively low, at (-1.22 eV), indicating that Li + After adsorption on the Co site surface, it is easy to migrate. In addition, Li + Adsorption energy at the peripheral cyanide sites. Figure 1 As shown in (b), the adsorption energy of the peripheral cyanide sites is much higher, which clearly indicates that Li + Transfer at the peripheral cyanide site is more difficult than transfer at the metal site. For convenience, monocyanophthalocyanine is used instead of CPF, and a series of structural Gibbs energy calculations are performed to illustrate the Li + Migration barriers on different metal surfaces ( Figure 1 Medium c and Figure 8-10 ). By analyzing Li + The migration potential energy surface shows that the migration is more likely to occur in the direction of N3 ring → pyrrole ring → benzene ring. In addition, the Li +The potential energy of lithium migration was found to be relatively low (1.57 kcal / mol) when the central metal is Co. + The surface migration of Figure 11-13 ). It is noteworthy that the polymerization of bisphthalocyanines exhibits a similar trend to that of monocyanophthalocyanines, further demonstrating the excellent Li + The transport and performance can be attributed to the Co sites.

[0052] The above results show that CoSAs-CPF is an ideal substrate for adsorbing lithium. Thanks to the role of different Lewis acid metal sites, CoSAs-CPF is more conducive to the migration of lithium, so we synthesized CoSAs-CPF, characterized its structure in detail, and used it as an artificial SEI film for high-voltage lithium metal.

[0053] The specific preparation method of CoSAs-CPF is provided below.

[0054] Example 1

[0055] A method for preparing CoSAs-CPF comprises the following steps:

[0056] 1,2,4,5-Tetracyanobenzene (TCNB) (0.1 g), cobalt chloride (36 mg) and 1,8-diazacyclo (5,4,0) undec-7-ene (DBU) (0.1 mL) were dissolved in ethylene glycol and N,N-dimethylformamide (DMF) (v:v = 9:1, total volume 10 mL) and reacted at 180 ° C for 5 days. After cooling to room temperature, the precipitate was collected by filtration and washed with water. The solid was dried to obtain CoSAs-CPF in the form of black powder.

[0057] Example 2

[0058] A method for preparing CoSAs-CPF comprises the following steps:

[0059] TCNB (0.2 g), cobalt chloride (50 mg) and DBU (0.1 mL) were dissolved in ethylene glycol and DMF (v:v = 9:1, total volume 15 mL) and reacted at 180 ° C for 2 days. After cooling to room temperature, the precipitate was collected by filtration and washed with water. The solid was dried to obtain CoSAs-CPF in the form of a black powder.

[0060] Example 3

[0061] A method for preparing CoSAs-CPF, compared with Example 1, changes the reaction temperature, comprising the following steps:

[0062] TCNB (0.1 g), cobalt chloride (36 mg) and DBU (0.1 mL) were dissolved in ethylene glycol and DMF (v:v = 9:1, total volume 20 mL) and reacted at 120 ° C for 5 days. After cooling to room temperature, the precipitate was collected by filtration and washed with water. The solid was dried to obtain CoSAs-CPF in the form of a black powder.

[0063] Example 4

[0064] A method for preparing CoSAs-CPF, compared with Example 1, changes the reaction time, comprising the following steps:

[0065] TCNB (0.1 g), cobalt chloride (36 mg) and DBU (0.1 mL) were dissolved in ethylene glycol and DMF (v:v = 9:1, total volume 8 mL) and reacted at 180 ° C for 2 days. After cooling to room temperature, the precipitate was collected by filtration and washed with water. The solid was dried to obtain CoSAs-CPF in the form of a black powder.

[0066] The CoSAs-CPF prepared in the above embodiments is similar. Taking Embodiment 1 as an example, the structure of the CoSAs-CPF prepared in Embodiment 1 is characterized. The characteristic peaks in the Fourier transform infrared spectrum are located at about 1547, 1697, 1711 and 1757 cm -1 Department Fig.14 ), indicating that a specific macrocyclic structure of phthalocyanine was successfully constructed. 13 C solid-state NMR further confirmed the carbon structure of CoSAs-CPF ( Fig.15 ). X-ray photoelectron spectroscopy (XPS) and synchrotron-based XANES spectroscopy ( Figure 3 The coordination environment of Co, such as valence state, coordination state, and bond configuration, was deeply identified in Figure ac. Compared with the corresponding reference samples (Co foil, Co2O3, Co3O4, and cobalt phthalocyanine (CoPc)), the Co k-edge XANES curve ( Figure 3 (b) shows that the front edge profile of CoSAs-CPF is similar to that of CoPc, with only a slight difference in intensity, indicating that Co exists in a homogeneous state in CoSAs-CPF and forms a Co-Nx coordination. The X-ray absorption fine structure (EXAFS) spectrum shows that Co-O (CoO as reference) and Co-N (CoPc as reference) are The dominant peak produced at has a similar absorption position to (CoPc) ( Figure 3 c), indicating the presence of a single Co atom site coordinated by N. In addition, in CoSAs-CPF, There is no peak belonging to the Co-Co metal bond at the bottom, which further verifies the atomic dispersion of Co atoms ( Figure 3Meanwhile, the significant scattering path signal of Co-N bond in the first coordination shell of CoSAs-CPF [χ(k), χ(R)] is located at [3.79, 1.25], while the weak scattering path signal of Co-C in the second coordination shell is located at [4.41, 2.23], which can be found in the wavelet transform of χ(k) spectrum ( Fig.16 ). In addition, the characteristic scattering path signal of Co-Co bonding in Cu foil located at [7.12, 2.14] was not observed in CoSAs-CPF, which again indicates the atomic dispersion of Co atoms in CoSAs-CPF. In summary, the Co K-edge XANES curves well elucidate the cooperative environment of Co sites in CoSAs-CPF, and the correlation analysis results of R space and the wavelet transform of χ(k) spectrum are also clearly proved, and the single atomic state of Co atoms is also proved.

[0067] At the same time, CoSAs-CPF was observed under atomic force microscopy (AFM) ( Figure 3 d), scanning electron microscopy (SEM) ( Fig.17 ) and transmission electron microscopy (TEM) ( Figure 2 Zhongehe Fig.18 ) show a two-dimensional slice morphology with uniform distribution of different elements. AFM acquisition of the thickness of CoSAs-CPF confirmed that its thickness was about 3.5-8nm ( Fig.19 ), corresponding to 10-18 atomic layers. In addition, it can be observed from SEM and TEM images that there is no aggregation of metal particles on the surface of CoSAs-CPF, indicating that Co is uniformly distributed on the surface of CoSAs-CPF at the atomic scale. Subsequently, the atomic structure of CoSAs-CPF was further studied using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). Figure 3 From the aberration-corrected HAADF-STEM image of CoSAs-CPF, it can be observed that there is no trace of aggregation ( Figure 3 f). Elemental mapping also shows that the coordinated Co atoms are fully atomized and highly uniformly distributed on the surface ( Figure 3 in gi).

[0068] Application Example 1

[0069] A method for preparing an artificial SEI film comprises the following steps:

[0070] The CoSAs-CPF prepared in Example 1 was dispersed in anhydrous DMF and subjected to strong ultrasonic treatment to form a uniform CoSAs-CPF nanosheet mixed solution (CoSAs-NSs). Figure 2As shown in (b), after filtering CoSAs-NSs on a polypropylene (PP) membrane, a simple roller pressing process was used to transfer CoSAs-NSs to the lithium surface to finally prepare CoSAs-CPF@Li.

[0071] CoSAs-CPF@Li was fabricated by a simple roll-pressing process ( Figure 2 (b) Optical photo of CoSAs-CPF@PP ( Fig. 20 ) showed that CoSAs-CPF was uniformly pumped onto the PP film, forming a dense film with a dark green (close to black) color. Subsequently, the CoSAs-CPF@PP surface containing CoSAs-CPF was rolled onto 100μm lithium metal to form CoSAs-CPF@Li, thus obtaining an artificial CoSAs-CPFSEI. Subsequently, the CoSAs-CPF@Li was cut into small discs with a diameter of 16mm for button cell assembly and testing ( Figure 21-22 ). It is worth noting that the contact angle of CoSAs-CPF@Li is significantly smaller than that of lithium foil, which indicates that CoSAs-CPF has better wettability to the electrolyte and further indicates that the artificial CoSAs-CPF SEI film has good chemical compatibility ( Fig.23 In addition, the X-ray photoelectron spectroscopy of CoSAs-CPF@Li was measured, indicating that it has good stability to lithium ( Figure 3 A and Figure 24-25 ).

[0072] Application Comparative Example 1

[0073] To further explore the induced behavior of different Lewis acid sites on lithium deposition, we synthesized NiSAs with isomorphous structures using the same method and prepared NiSAs-CPF@Li. Subsequently, detailed electrochemical tests were carried out to evaluate its practical application potential in lithium metal batteries.

[0074] The effect of artificial CoSAs-CPF SEI on lithium deposition behavior and cycle stability was evaluated by constant current charge-discharge experiments of Li||Li symmetric cells assembled with CoSAs-CPF@Li and NiSAs-CPF@Li. -2 The constant current density and 1.0 mAh cm -2 Under the surface capacity ( Figure 4 In a), the constant current cycling curve of the artificial CoSAs-CPF SEI symmetric battery shows outstanding cycling stability and low voltage fluctuation of ~40mV within 3500h. At the same time, the CoSAs-CPF@Li, NiSAs-CPF@Li and bare lithium symmetric batteries were further tested at 0.5~10mAcm -2The rate capability is 0.5~10mAh cm -2 ( Figure 4 (b). It can be clearly seen that the voltage polarization increases with the increase of current density, and CoSAs-CPF@Li shows the slightest voltage polarization at different current densities, further highlighting its superior rate performance and promoting uniform lithium deposition. X-ray photoelectron spectroscopy (XPS) analysis of the cycled lithium anodes at different etching times (0, 60, 120 and 240s) was performed to further analyze the chemical composition of the newly formed SEI. It is well known that inorganic LiF improves the uniformity of lithium deposition and promotes the stability of SEI, while the inorganic phase CF has the opposite effect. From Figure 4 The fitting results of c and d show that the Li-F content of the cycled CoSAs-CPF@Li is significantly higher than that of the cycled bare lithium anode, and the CF content is significantly lower than that of the cycled bare lithium anode. The inorganic Li-F is evenly distributed at each etching depth, indicating that the stable artificial CoSAs-CPF SEI makes TFSI - The anion preferentially decomposes to LiF, while the Li-F peak of the cycled bare lithium anode is low, implying only a small amount of TFSI. - In other words, CoSAs-CPF@Li provides the ability to inhibit further electrolyte decomposition and maintain interfacial stability. After rate cycling, severe cracks and unevenness appeared on the surfaces of the cycled NiSAs-CPF@Li and bare lithium, which is due to the Li + In contrast, the surface of cycled CoSAs-CPF@Li remains relatively smooth, which is consistent with the rate performance ( Figure 4 (eg).

[0075] High LFP loading (20 and 30 mg cm -2 ) to explore the potential application and practical feasibility of artificial SEI. The results show that when the LFP loading is 20 mg cm -2 The specific capacity of CoSAs-modified batteries is as high as 144 mAh g at 1 °C. -1 , Coulombic efficiency of 99%, and almost no capacity drop after an ultra-long life of 1000 cycles (98.6% capacity retention) ( Figure 5 In contrast, the initial capacities of bare lithium and NiSAs-modified lithium anodes are similar, but the capacities drop sharply after 200 and 280 cycles, respectively. This undoubtedly indicates that the uncontrollable growth of LFP||NiSAs-CPF@Li and LFP||bare lithium dendrites breaks out to different degrees. -2 At ultra-high LFP loading, the LFP||CoSAs-CPF@Li battery system provides 133mAh g -1and showed only a slight capacity decay trend after 533 consecutive cycles ( Figure 5 b). These batteries were then disassembled and replaced with new CoSAs-CPF@Li to reassemble new batteries. The restarted batteries still maintained a stable life of 850 cycles under the same conditions. Such excellent results at ultra-high LFP loading are uncommon and better than most reports. This further reflects that the designed artificial SEI (CoSAs-CPF) can also effectively induce uniform lithium deposition and inhibit electrolyte decomposition and lithium dendrite growth at ultra-high LFP loading.

[0076] We further investigated the potential application of CoSAs-CPF@Li in NCM811 high energy density batteries. The high nickel ternary cathode (NCM811) and different modified lithium metals were assembled into batteries, which were labeled as NCM811||CoSAs-CPF@Li, NCM811||NiSAs-CPF@Li and NCM811||bare lithium (NCM811 loading was 10 mg cm -2 ), and then the long-term cycling performance of these batteries was evaluated. Figure 5 As shown in Figure c, after two cycles of activation at 0.1C, the initial capacity of NCM811||CoSAs-CPF@Li at 1C is 166 mAh g -1 , which is better than NCM811||NiSAs-CPF@Li and NCM811||bare lithium (159 and 146 mAh g -1 ). It is worth noting that NCM811||CoSAs-CPF@Li can still maintain up to 80% of the discharge capacity after a long period of 800 cycles and has a near-perfect Coulombic efficiency (~99.4%), indicating that the electrode material is efficiently utilized and the charge and discharge efficiency is guaranteed. In contrast, the capacity retention rates of NCM811||NiSAs-CPF@Li and NCM811||bare lithium batteries are less than 80% at 300 and 160 cycles, respectively. The discharge capacities of NCM811||CoSAs-CPF@Li at current densities of 0.2, 0.5, 1, 2, 3, 4, and 5C are 206, 196, 188, 180, 173, 164, and 157 mAh g, respectively. -1 ( Figure 5 More importantly, by increasing the loading of NCM811 to 20 mg cm -2 To meet higher challenges in practice ( Figure 5 e), after one cycle of activation at 0.1C, NCM811||CoSAs-CPF@Li gave 166 mAh g at 1C. -1The initial capacity of 1.54 W was 2.34 W, and the excellent stable cycling over 450 cycles with a capacity retention of 85.6% at 1C was achieved, providing high Li + utilization and 99% Coulombic efficiency. Figure 5 In Figure 5, the performance is highly competitive compared to other NCM811 cathodes with modified lithium anodes.

[0077] Digital photos show that the electrode size of the pouch battery is 6cm×8cm ( Figure 6 The cycling performance of NCM811||CoSAs-CPF@Li pouch cells was studied ( Figure 6 b and c). Highly loaded cathode (NCM811: 20 mg cm -2 ) The discharge capacity of NCM811||CoSAs-CPF@Li battery at 0.1C is 210 mAh g -1 (4.2mAhcm -2 ), the first cycle discharge capacity at 0.5C is as high as 190mAh g (198mAhg -1 ), the discharge capacity after 120 cycles is 179 mAh g -1 , the capacity retention rate is 90.4%. This provides a promising strategy for the design of high energy density and high voltage lithium metal batteries. Ultrasonic imaging technology is an interface-sensitive method used to test the wetting state and gas generation of pouch cells. The ultrasonic signal will be significantly attenuated in the vacuum or gas at the electrode interface than in the solid. The ultrasonic signal changes from red to blue, indicating that the signal intensity changes from high to low. NCM811||bare lithium and NCM811||NiSAs-CPF@Li pouch cells show unevenness after cycling. As the number of lithium dendrite cycles increases, the image gradually turns blue, indicating the growth and severe powdering of lithium dendrites ( Figure 6 However, as the number of cycles increases, the interface in the NCM811||CoSAs-CPF@Li bag remains in its initial state, indicating that the presence of the artificial SEI film stabilizes the lithium metal interface and prolongs the cycle life of the high-voltage battery ( Figure 6 (f)

[0078] The instability of the bare lithium metal interface leads to uncontrollable lithium dendrite growth. By disassembling the NCM811 lithium pouch cell, a top view SEM image of the cycled lithium anode was obtained after 60 cycles. Lithium dendrite growth is obvious on the cycled bare lithium foil and NiSAs-CPF@Li. Many cracks and powder appeared on the lithium metal surface with NiSAs-CPF@Li added ( Figure 6 g and h). For the cycled CoSAs-CPF@Li, it is relatively flat ( Figure 6 i), high mechanical strength and uniform Li +The flux effectively inhibits the growth of lithium dendrites and forms a stable contact interface.

[0079] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.

Claims

1. A method for preparing an artificial solid electrolyte interface for a high-voltage lithium metal battery, characterized in that: The cobalt-containing two-dimensional conjugated phthalocyanine framework is dispersed in DMF and subjected to ultrasonic treatment to form a nanosheet mixed solution; after filtering the nanosheet mixed solution, the nanosheet is transferred to the lithium surface by a roller pressing process to obtain an artificial solid electrolyte interface of a high-voltage lithium metal battery; the preparation method of the cobalt-containing two-dimensional conjugated phthalocyanine framework comprises the following steps: The cobalt-containing two-dimensional conjugated phthalocyanine framework is prepared by using 1,2,4,5-tetracyanobenzene and a soluble cobalt salt as raw materials and 1,8-diazacyclo(5,4,0)undec-7-ene as a catalyst through a solvothermal reaction in an organic solvent.

2. The preparation method according to claim 1, characterized in that: Co in 1,2,4,5-tetracyanobenzene and soluble cobalt salts 2+ The molar ratio of 1,2,4,5-tetracyanobenzene and 1,8-diazacyclo(5,4,0)undec-7-ene is 2:

1.

3. The preparation method according to claim 1, characterized in that: The reaction temperature is 100-240°C, and the reaction time is 2-6 days.

4. The preparation method according to claim 1, characterized in that: The soluble cobalt salt is one of cobalt chloride, cobalt nitrate and cobalt sulfate.

5. The preparation method according to claim 1, characterized in that: The organic solvent is a mixed solvent prepared by mixing ethylene glycol and DMF in a volume ratio of 1-9:

1.

6. The preparation method according to claim 5, characterized in that: The usage ratio of 1,2,4,5-tetracyanobenzene to the organic solvent is 0.1 g:5-30 mL.

7. An artificial solid electrolyte interface for a high-voltage lithium metal battery prepared by the preparation method according to claim 1.

8. Use of the artificial solid electrolyte interface of a high-voltage lithium metal battery according to claim 7 in a high-voltage lithium metal battery.

Citation Information

Patent Citations

  • Cobalt phthalocyanine covalent organic framework desulfurization catalyst as well as preparation method and application thereof

    CN117299212A